CALCULATE THE ESTIMATED LOADING TIME OF CAUSTIC SODA ACCORDING ON THE AMOUNT OF CAUSTIC SODA LOADED ON MT AKRA 102. - Guntoro, Herlan; Yudhiyono; Parulian, Daniel (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) STIP Jakarta, 2023)
Sodium Hydroxide is a chemical with the chemical formula NaOH. At room temperature Sodium Hydroxide is a white powder (ATSDR, 2014), known as Caustic Soda, because it gives a burning effect on the skin and causes yellow spots on fabrics and paper (PHE, 2019). Caustic soda is included in the category of hazardous materials categorized by the International Maritime Organization when transported by ship. In order to reduce costs, it is sought to streamline the loading time of Caustic soda into the ship without ignoring the established safety procedures. For this reason, it is necessary to calculate the loading time, to ensure that the time required during the implementation of loading activities is not too much different from the predetermined time. To estimate the loading time can be done by calculating the maximum transfer rate of caustic soda can also be calculated based on time reports from previous loading activities. It is expected that with an estimate of loading time that can be calculated accurately based on the amount of caustic soda loaded, the calculation of costs associated with loading activities can be estimated more accurately.